Particle finite element method implementation for large deformation analysis using Abaqus - Yuan, Wei-Hai; Wang, Hao-Cheng; Zhang, Wei; Dai, Bei-Bing; Liu, Kang; Wang, Yuan (Acta geotechnica, 2021)
In this study, a simple PFEM approach for analyzing large deformation problems in geotechnical practice is implemented in the commercial FEM package Abaqus. The main feature of the proposed Abaqus-PFEM approach lies in its capability to absorb the advantages of the functionality available in Abaqus and integrate them into PFEM with a single Python script, which leads to a considerable reduction in coding work. By utilizing the built-in functions in Abaqus to fulfil the standard incremental FEM analysis, as well as the powerful mesh-to-mesh solution mapping technique, the proposed Abaqus-PFEM approach allows for the large deformation analysis automatically running with a single Python script and requires no intervention from the user. The accuracy of the proposed Abaqus-PFEM approach is firstly validated through a simple elastic cantilever beam bending problem. Then, the performance and robustness of the proposed Abaqus-PFEM approach are further examined by three illustrative numerical examples: penetration of rigid footing, penetration of T-bar and pipeline–soil interaction problem. The numerical results demonstrate that the proposed Abaqus-PFEM approach as a powerful and easily extensible numerical tool is capable of handling large deformation and soil–structure interaction problems in geotechnical engineering, and consequently, it offers an alternative way to tackle such problems.